Adaptasi dan Uji Validitas Konstruk Social Media Fatigue Scale di Indonesia - Sardinawati, Mustika Mauliddiana; Hilmana, Primaditha Noorrizqyka Putri; Sari, Sandra Mutiara; Pratiwi, Windy Mutia; Saefudin, Muhammad Arif (Journal of Research and Measurement in Psychology: JPPP, 2026)
Research examining the construct validity of the Social Media Fatigue Scale (SMFS) in the Indonesian context remains limited. This study aimed to test the construct validity of the SMFS based on its three-dimensional structure cognitive, behavioral, and emotional to examine the consistency of its dimensionality among Indonesian adults. Data were collected from 284 participants aged 18 years and above in Indonesia. Data analysis was conducted using confirmatory factor analysis (CFA) with maximum likelihood estimation. The results demonstrated that the SMFS tends to be a multidimensional measurement instrument that is suitable for use in the Indonesian context. Model fit indices met acceptable criteria, as indicated by SRMR (< .08), CFI (>.90), and TLI (> .90), although RMSEA was within the acceptable fit range (< .10). All items showed significant factor loadings on their respective dimensions, supporting the proposed three-factor structure of social media fatigue. Overall, the findings indicate that the Indonesian version of the SMFS has satisfactory construct validity and can be reliably used to assess social media fatigue among Indonesian adults. The availability of a culturally adapted and psychometrically sound instrument is expected to support future research and psychological interventions related to social media use and well-being.